Online discussion: enhancing students’ critical thinking skills - Rathakrishnan, Mohan; Ahmad, Rahayu; Choo, Ling Suan (IP Publishing LLC, 2017)
Online discussion has become one of the important strategies for the teacher to teach the students to think critically when conveying their ideas and become more proactive and creative. In this paper, padlet online discussion communication was conducted to examine its effectiveness in enhancing critical thinking. In this study, there are two types of critical thinking: macro and micro critical thinking. A total of 70 Universiti Utara Malaysia Management Foundation Programme students involved in this experimental research design. The students in treatment class are divided to few groups. Every group uses padlet online discussion to discuss the topic given. All the group members discuss and write their ideas in padlet. Ideas that are posted in padlet will be displayed in front of the class so that the entire group in the treatment class could see the given ideas. Paul’s (1993) model was used to analyze student’s macro and micro critical thinking in padlet online discussion and communication. The finding shows that students who used padlet online discussion backchannel communication have greater macro and micro critical thinking level than students who do not use online discussion.